Neuropsychological and clinical correlations of optical coherence tomography findings in patients with schizophrenia - SAKALLI KANİ, AYŞE; ŞAHİN ÇAM, CANSUN; AKKAYA TURHAN, SEMRA; TOKER, AYŞE EBRU; YILDIZ, MESUT (My University, 2023)
Objective: There are increasing studies examining retinal fiber layer (RNFL) and ganglion cell layer (GCL) thinning in patients with schizophrenia. However, the results are controversial, and clinical and cognitive reflections of these findings remain unclear. With this study, we aim to examine retinal abnormalities and establish correlations with cognitive and clinical parameters. Methods: In this cross-sectional study, we examined 29 patients with schizophrenia and 13 age and gender-matched healthy controls. All participants underwent psychometric assessment, neuropsychological tests, and optical coherence tomography (OCT) measurements. The retinal fiber layer and ganglion cell layer thickness were used as retinal parameters. Results: Five patients dropped out during the OCT measurement process, 24 patients with schizophrenia and nine healthy controls were included in the analysis. There was no statistically significant difference between groups in measuring retinal nerve fiber layer or ganglion cell layer thicknesses. The verbal fluency test score negatively correlated with left RNFL superior (ρ = – .422, p <.05). STROOP response duration positively correlated with right RNFL on average (ρ = .551, p <.05), left RNFL on average (ρ = .498, p <.05), right RNFL superior (ρ = .507, p <.05), left RNFL superior (ρ = .461, p <.05) and right RNFL temporal values (ρ = .434, p <.05). STROOP response error was also positively correlated with right RNFL temporal thickness (ρ = .430, p <.05). STROOP response duration was positively correlated with right GCL total (ρ = .646, p <.01), right GCL superior (ρ = .658, p <.01) and right GCL inferior (ρ = .596, p <.01) thickness. Conclusion: We did not find a significant relationship between reduced RNFL or GCL thickness and cognitive impairment. However, we had several positive correlations between cognitive task scores and RNFL and GCL thicknesses. Additionally, our study did not correlate symptom severity and clinical severity parameters with reduced RNFL or GCL thickness
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)